Challenges of Processing Digital-Based Library Materials in School Libraries - Nuraeni, Dhila Sri; Rusmana, Agus; Anwar, Rully Khairul (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2024)
This research aims to reveal the challenges presented by the development of library automation in school libraries. This research aims to explain and describe digital-based library material processing activities in the SMAN 1 library. This research uses descriptive qualitative research methods. The results of the research are the challenges they face in the form of a lack of quantitative and quality human resources. The available facilities are inadequate, especially to support digitalization processes such as implementing OPAC. This is due to frequent changes in collections based on curriculum and government policies.